Physical and biological insights of nanostructured Ti-8Mn alloy for coronary drug eluting stent material - Soliman, Alaa Mohyeldin (AUC Knowledge Fountain, 2019)
According to the World Health Organization (WHO), cardiovascular diseases (CVDs) are the main cause of death worldwide. Coronary Artery Disease (CAD) is the common cause of heart failure. In CAD, lipids and fats that are circulating with the blood may get accumulated within the injured arteries' walls and restrict the blood flow to the myocardium, which in turn results in atherosclerosis. Since the approval of Drug Eluting Stents (DES) by the Food and Drug Administration (FDA) as a treatment option for CAD, multidisciplinary research is being conducted to introduce biomaterials with adequate physical properties as well as excellent clinical outcomes. In this regard, different surface treatment approaches are used to optimize the properties of biomaterials rendering them with enhanced mechanical properties as well desired biological response. Different nickel-based metals and polymer coatings currently used in stent market have increased the recurrence of in-stent restenosis and stent failure. In this study, Ti-8Mn alloy was used to fabricate nanostructured surface that can be used for drug eluting stents to overcome the hypersensitivity of metals currently used in stent making as well as introducing a new built-in nano-drug reservoir instead of polymer coatings. Two different systems were studied: pure Ti and Ti-8Mn. The materials were characterized using field emission electron microscope (FESEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), roughness, wettability and surface energy measurements. Nanoindentaion was also used to evaluate the mechanical properties of the nanotubes as well as their stability. In-vitro cytotoxicity and cell proliferation assays were used to study the effect of the nanotubes on the cell viability. At the end, computational insights on the blood compatibility using band gap model comparing the band gap of the materials under study with the HOMO of the Fibrinogen to study the possibility of the charge transfer that control the blood clotting was performed. In addition, the drug loading capacity of the materials was studied using acetyl salicylic acid as a drug model.